2020
DOI: 10.1016/j.trd.2020.102324
|View full text |Cite
|
Sign up to set email alerts
|

Impact analysis of climate change on rail systems for adaptation planning: A UK case

Abstract: Climate change poses critical challenges for rail infrastructure and operations. However, the systematic analysis of climate risks and the associated costs of tackling them, particularly from a quantitative perspective, is still at an embryonic phase due to the kaleidoscopic nature of climate change impacts and lack of precise climatic data. To cope with such challenges, an advanced Fuzzy Bayesian Reasoning (FBR) model is applied in this paper to understand climate threats of the railway system. This model ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Accordingly, climate risks were assessed based on their timeframes of climate threats, occurrence frequencies, the severity of consequences, and resilience of infrastructure to climate change with minimum uncertainty and loss of objective information (Wang et al, 2020).…”
Section: Asset Management For Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, climate risks were assessed based on their timeframes of climate threats, occurrence frequencies, the severity of consequences, and resilience of infrastructure to climate change with minimum uncertainty and loss of objective information (Wang et al, 2020).…”
Section: Asset Management For Climate Changementioning
confidence: 99%
“…Meanwhile, the uncertainty issues on climate change had been addressed by another group of scholars (e.g., Randrianarisoa & Zhang, 2019;Wang et al, 2020), in recent years, by studying the scale and timing of investment and relevant issues in climate adaptation in a competitive port market. Through establishing a two-period real options game model, it was found that the probability of climate threat occurrence, and the level of competition the information obtained could influence the timing of investment (Randrianarisoa & Zhang, 2019).…”
Section: Asset Management For Climate Changementioning
confidence: 99%
“…However, the findings of these investigations are not being applied by the railway stakeholders because of numerous challenges and barriers, such as knowledge and awareness about climate change impacts, shortage of capital investment, the nonexistence of policies, shortage of resources and time, etc. [22,23]. Moreover, it is difficult to comprehend the impacts of climate change since it changes with geographical locations, and in many cases, there is a lack of studies of risk consequences and impact assessments for the region.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting qualitative analysis is a rigorous and time-consuming process; for instance, see Canada [59], UK [23], USA [60][61][62][63], Germany [64], Tanzania [65], Malaysia [55], Baltica [66], and Sweden [56] that are not entirely focused on research gaps identified above from the operation and maintenance of the railway.…”
Section: Introductionmentioning
confidence: 99%
“…Roads and railways are sensitive to climate-related events such as intense rainfall and flooding causing landslides, damaged bridge foundations, overloaded track drainage, flooded tracks and derailment risks, already resulting in high costs [ 1 , 2 , 3 , 4 ]. The costs are expected to increase as extreme weather events will become more frequent and severe due to climate change [ 5 ].…”
Section: Introductionmentioning
confidence: 99%